Pemanfaatan Game Interaktif QuizWhizzer Berbasis Gamifikasi terhadap Tingkat Minat Belajar Murid SMK Program Keahlian Kuliner - Frenika Yugita Pratiwi; Lismi Animatul Chisbiyah; Erna Tungga Dewi (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study has purposes to examine the application of gamification-based interactive game QuizWhizzer in Basic Culinary learning and to analyze the level of learning interest of tenth-grade vocational high school students’ learning interest. The study applied a quantitative approach using a descriptive survey method. The subjects of this research consisted of 35 students from Class X Culinary Industry 1 at SMKN 3 Malang, selected through a purposive sampling technique. Data were collected through observations and questionnaires based on four indicators of learning interest, namely interest, attention, involvement, and enjoyment. The research instrument was a Likert-scale questionnaire that had been validated by a culinary subject teacher as an expert judgment. The data were analyzed using descriptive quantitative techniques by measuring respondents’ answers by precentage. The results of the research on the use of the gamification-based interactive game QuizWhizzer showed that the level  of  students’ learning interest was very good at the beginning of Basic Culinary learning. The observation results indicated that the interest indicator reached 91%, attention 89%, involvement 92%, and enjoyment 93%, all categorized as very good. Meanwhile, the questionnaire results showed that all four indicators achieved very good categories, with the highest percentage found in the enjoyment indicator at 88%. Therefore, the use of gamification-based QuizWhizzer is considered effective in creating a more enjoyable, interactive, and student-centered learning environment, while supporting the development of high learning interest among student’s.